2019
DOI: 10.1002/jip.1523
|View full text |Cite
|
Sign up to set email alerts
|

Examining modus operandi in stranger child abduction: A comparison of attempted and completed cases

Abstract: Existing inquiries purporting to study and describe offender behaviour in stranger child abduction (SCA) have utilised an overly narrow definition of modus operandi (MO), focusing only on very outset of the offence. The study aims to reflect changes that occur as the offence proceeds and to examine whether differentiating between attempted and completed cases can provide greater understanding of MO in SCA. The MO utilised by offenders in 78 cases of SCA retrieved from publicly available U.K. sources were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In these cases, 60% of vehicles were owned by the offender or were available to them through routine access. Building on this research, Collie and Greene (2019) identified that vehicle use was specifically associated with offenders who adopted a manipulative MO.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In these cases, 60% of vehicles were owned by the offender or were available to them through routine access. Building on this research, Collie and Greene (2019) identified that vehicle use was specifically associated with offenders who adopted a manipulative MO.…”
Section: Resultsmentioning
confidence: 94%
“…While three studies examined NFA collectively (e.g. Erikson and Friendship, 2002; Gallagher et al , 2008; Park and Cho, 2019) and two studies solely examined stranger abductions (Collie and Greene, 2017, 2019), the remaining articles differentiated NFA cases based on relationship type. Most of these studies did so using a stranger/acquaintance (or stereotypical/legal definition, see Asdigian et al , 1995) dichotomy (Boudreaux et al , 1999; Brown and Keppel, 2012; Miller et al , 2008; Tillyer et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…e Modus Operandi changes based on the offender's criminal conduct and interaction with the surrounding such as time, date, and location of crime. Moreover, it evolves based on how the offender reaches his/her victim [28,29].…”
Section: Traditional Criminal Profiling and Cybercrime Profilingmentioning
confidence: 99%
“…Although studies on the subject of missing children and child abduction have increased, it is not enough (1,(12)(13)(14). In the studies, the challenges of the missing person investigations, the behaviour of the missing people, the geographic information in the missing investigations, the importance of the risk assessment and immediate response were discussed and suggestions were made to help the police investigations (1,5,8,13,(15)(16)(17). While these studies generally mention the investigation of missing persons, they rarely touch on the characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%